Development of point-to-point OCDMA system for metropolitan area network - Liyana Dhamirah M. Zamani (Universiti Malaysia Perlis, 2008)
Future telecommunication systems and networks are expected to provide a variety of integrated broadband services to the customers. There has been a tremendous interest in applying Code Division Multiple Access (CDMA) techniques to fiber optic communication systems. The advantages of OCDMA in networks are compelling and worthy of further investigation in the goal of realizing an extensive, flexible, high throughput and easily managed optical telecommunication infrastructure. The performance of any Optical CDMA (OCDMA) system strongly depends on the codes properties. In optical CDMA systems, the detection process affects the design of transmitters and receivers. This project is presented a development of point to point OCDMA system for metropolitan area network application. In this work, Double Weight (DW) code and AND subtraction technique was implemented in system. The performance of the system is shown through simulated results of the bit error rate (BER) and eye pattern of different design parameters.